Assistant teachers for pupils with special educational needs in the Czech Republic – presentation of selected particular research results - Michalík, Jan; Chrastina, Jan; Maštalíř, Jaromír; Baslerová, Pavlína (Social Welfare: Interdisciplinary Approach, 2015)
The profession of an assistant teacher (AT) deserves due attention in terms of methodological, personnel, legislative and professional discourse. The position of AT was established in the Czech Republic already in 2005; however, research and scientific findings providing relevant practical data (in the form of general research studies) are still missing. The paper presents a concept of a national research study performed in February – March 2015 and particular results focusing on the description of sociodemographic distributions and selected aspects of labour-law relationships (and their attributes) in terms of the function of AT. The paper also includes an interpretative view of the results by means of suggested practical measures in the area of operation, competences and especially legislation. The research study used a quantity-based approach to investigate the research phenomena. The data collection method was a questionnaire of an own design, which was – regarding the number of ATs in the Czech Republic – administered in an electronic form. The data were then classified, analysed and statistically tested. This is the first communication of an extensive research report. It describes the initial domain of sociodemographic characteristics and the first research – labour-law aspects: employment contract, type of employment, length of employment, amount of remuneration and related aspects.